The Influence Of Supply Chain Management On Consumer Loyalty At CV Jaya Plafon, Gunungsitoli City - Hulu, Juli Herdiman; Kakisina, Sophia Molinda; Harefa, Idarni; Zebua, Serniati (Universitas Dehasen Bengkulu, 2025)
This study aims to analyze the effect of supply chain management on consumer loyalty at CV Jaya Plafon, Gunungsitoli City. The background of the study indicates a decline in consumer loyalty, indicated by a consistent downward trend in the number of customers purchasing cement and iron products from March to June 2025. This decline is strongly suspected to be related to suboptimal supply chain management, such as stockouts, late deliveries, and unclear product information.The research method used was quantitative. Data were collected through questionnaires distributed to 88 respondents, who were CV Jaya Plafon consumers who met the purposive sampling criteria. The independent variable in this study was Supply Chain Management (X), with indicators of inventory availability, product variety, low cost, and product quality. The dependent variable was Consumer Loyalty (Y), with indicators of repeat purchases, customer retention, and recommendations. Data were analyzed using simple linear regression with SPSS version 27 software, preceded by validity, reliability, normality, and heteroscedasticity tests. The results indicate that supply chain management has a positive and significant effect on customer loyalty at CV Jaya Plafon in Gunungsitoli City. This is evidenced by the calculated t-value of 7.771, which is greater than the t-table of 1.98793, and the significance value of 0.000, which is less than 0.05. The coefficient of determination (R²) of 0.412 (41.2%) indicates that 41.2% of the variation in customer loyalty can be explained by supply chain management, while the remaining 58.8% is influenced by factors outside the research model. These findings underscore the importance of effective supply chain management in building and maintaining customer loyalty in the building materials retail sector.